Capacity Building for the Mappetajang Village Community through Agroecotourism Literacy Based on the Geoecology of the Highlands - Iriansa iriansa; Andi Jumardi; Masluki Masluki; Mutmainnah Mutmainnah (ABDISAINS, 2026)
Mappetajang Village is one of the villages lagging behind in terms of village development index, but it has high natural potential in realising sustainable development goals, especially in terms of horticultural agriculture and tourism potential. This community service activity aims to improve the literacy of the community and village government in optimising this potential through a participatory approach. The community service was carried out through socialisation activities, focus group discussions and perception surveys of 54 respondents. The impact of the community service was analysed using thematic analysis and descriptive statistics. The results of the community service showed an increase in community understanding of horticultural potential (40%) and agrotourism (32%), with a high level of interest in its development. The main constraints included limited technical skills (42%), capital (33%), and infrastructure (25%). The main recommendations included cultivation training, digital market access, and collaboration with stakeholders. The implementation of a holistic strategy is expected to encourage the transformation of the village economy towards inclusive and sustainable economic resilience